1998
DOI: 10.3109/10837459809028493
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tertiary Butyl Alcohol and Volatile Salts on the Sublimation of Ice from Frozen Sucrose Solutions: Implications for Freeze-Drying

Abstract: The purpose of this work was to investigate the phase behavior of tertiary butanol (TBA) and volatile ammonium salts in frozen mixtures with some commonly used excipients and the efficacy of such volatile additives in accelerating the sublimation of ice from frozen solutions. Differential scanning calorimetry was employed to determine first-order phase transformations and glass transition temperatures in binary and ternary mixtures. Ice sublimation rates were studied by conventional freeze-drying and mass loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…They provide an exhaustive list of examples from research laboratories as well as commercially manufactured products freeze-dried from aqueous-organic cosolvent systems. Among the advantages conferred have been increased solubility of hydrophobic drugs in the prelyo solution, (6) decreased drying time, (2,7) improved product stability (8,9) and reconstitution characteristics (10,11). The incorporation of isopropanol (IPA) as a colvent increased the crystallinity of cefazolin sodium in the lyophile (12).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They provide an exhaustive list of examples from research laboratories as well as commercially manufactured products freeze-dried from aqueous-organic cosolvent systems. Among the advantages conferred have been increased solubility of hydrophobic drugs in the prelyo solution, (6) decreased drying time, (2,7) improved product stability (8,9) and reconstitution characteristics (10,11). The incorporation of isopropanol (IPA) as a colvent increased the crystallinity of cefazolin sodium in the lyophile (12).…”
Section: Introductionmentioning
confidence: 98%
“…However, the role of TBA in increasing the crystallinity of drugs has not been explored. Ni et al obtained needle shaped drug crystals after lyophilizing an antitumor drug from pure TBA (9), while "erratic" crystallization of lactose from a TBA-water formulation during lyophilization has been reported (7).…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary butyl alcohol (TBA) is one of the most popular solvents used in freeze-dried formulations. Freezing and freeze-drying behavior of ingredients in solutions containing TBA has been evaluated (8)(9)(10)(11). Ni et al have demonstrated that TBA improved the stability of an antitumor drug by creating needle-shaped crystals during the freeze-drying process (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although most lyophiles are made from aqueous solution, lyophilization with pure organic solvent (3,4) or organic/water co-solvents (5)(6)(7)(8)(9)(10)(11)(12)(13) were reported in some cases where such solvents provided process or formulation advantages, such as improved drug stability (3,4), short drying time (6,7), and increased solubility of hydrophobic drugs (10,13).…”
Section: Introductionmentioning
confidence: 99%